2020
DOI: 10.1002/aqc.3507
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of plastic ingestion by pole‐caught pelagic predatory fish from O'ahu, Hawai'i

Abstract: 1. Although the frequency of occurrence of plastic ingestion in the large-sized dolphinfish and tunas taken by the Hawai'i longline fishery is very low (frequency

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Likewise, there were no observed negative effects of litter e.g. through entanglement or ingestion (Hyrenbach et al 2013;Vanderwerf and Young 2014) despite part of the mainland monitoring sites encompassing a disused refuse dump.…”
Section: Causes Of Breeding Failurementioning
confidence: 95%
“…Likewise, there were no observed negative effects of litter e.g. through entanglement or ingestion (Hyrenbach et al 2013;Vanderwerf and Young 2014) despite part of the mainland monitoring sites encompassing a disused refuse dump.…”
Section: Causes Of Breeding Failurementioning
confidence: 95%
“…Macroplastic ingestion has been documented in many tuna species including yellowfin (Thunnus albacares) (Chagnon et al, 2018;Fujieda et al, 2014;Manooch and Mason, 1983;Sajikumar et al, 2013), bluefin (Thunnus thynnus) (Romeo et al, 2015;Varela et al, 2022;Yick and Travers, 2022), blackfin (Thunnus atlanticus) (Manooch and Mason, 1983), the little tunny (Euthynnus alletteratus) (Manooch et al, 1985), skipjack (Katsuwonus pelamis) (Hyrenbach et al, 2021;Neto et al, 2020), bigeye (Thunnus obesus) (Fujieda et al, 2014), and albacore (Thunnus alalunga) (Hyrenbach et al, 2021;Romeo et al, 2015) tunas. Both swordfish (Xiphias gladius) (Romeo et al, 2015) and the black marlin (Makaira indica) (Fujieda et al, 2008) have been also been documented to ingest macroplastic litter.…”
Section: Tuna and Billfishmentioning
confidence: 99%
“…In the Mediterranean, Romeo et al (2015) found that 32.4 % of bluefin tuna (Thunnus thynnus) and 12.5 % of swordfish (Xiphias gladius) caught in the Mediterranean contained macroplastic fragments in their stomachs (Romeo et al, 2015). Plastic objects were generally fragments or sheets (Hyrenbach et al, 2021), such as pieces of plastic bag (Sajikumar et al, 2013), sweet and food wrappers (Varela et al, 2022) and fragments of food containers (Yick and Travers, 2022).…”
Section: Tuna and Billfishmentioning
confidence: 99%